Prevalence and characteristics of supernumerary teeth in a non-syndromic South Indian pediatric population - Rajesh T Anegundi; Veeresh S Tegginmani; Prashant Battepati; Anand Tavargeri; Shruthi Patil; Vijay Trasad; Garima Jain (Wolters Kluwer Medknow Publications, 2014)
Background: Supernumerary teeth are one of the most widely reported and significant anomaly in patients affecting the primary and early mixed dentition. Aim: To describe the distribution and characteristics of the supernumerary teeth in South Indian population of paediatric patients. Design: In a 12 year retrospective study, a total of 63,569 patients up to the age of 14 years who visited our department between June 2003 and May 2013 were revised.790 cases of supernumerary teeth were found. Patients were evaluated for age, sex, site, status of dentition, number, position, orientation and type of supernumerary teeth. Statistical analysis was carried out using chi square test. Results: 790 subjects with supernumerary teeth (481 males and 309 females) were detected, revealing male-female ratio of 1.55:1.The most common supernumerary teeth were mesiodens (82.28%), the most common site was the anterior maxilla (92.53%)region. Majority of patients had a single erupted supernumerary oriented straight in the arch. Patients in mixed dentition stage reported with maximum number of supernumerary teeth. Conclusions: The prevalence of supernumerary teeth in non syndromicSouth Indian paediatric population is 1.24% with slight male predilection and conical mesiodens being the commonest.